2018
DOI: 10.1016/j.niox.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body posture alter plasma nitrite but not nitrate concentration in humans

Abstract: Changing body posture causes rapid and consistent alterations in plasma [NO]. Researchers should therefore carefully consider the effect of posture when measuring this variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Nitrite and nitrate concentrations were evaluated in plasma and in the mouth rinse supernatants. Plasma samples were thawed and deproteinized (200 μL of the sample, 400 μL of zinc sulphate in deionized water at 10% weight/volume and 400 μL of 1 M sodium hydroxide in deionized water) for the determination of nitrate in order to avoid scum interferences during the determination [ 35 ]. The determination of nitrate and nitrite in the mouth rinse supernatants and of nitrite in plasma were performed directly without deproteinization.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrite and nitrate concentrations were evaluated in plasma and in the mouth rinse supernatants. Plasma samples were thawed and deproteinized (200 μL of the sample, 400 μL of zinc sulphate in deionized water at 10% weight/volume and 400 μL of 1 M sodium hydroxide in deionized water) for the determination of nitrate in order to avoid scum interferences during the determination [ 35 ]. The determination of nitrate and nitrite in the mouth rinse supernatants and of nitrite in plasma were performed directly without deproteinization.…”
Section: Methodsmentioning
confidence: 99%
“…The high levels of urinary nitrite found (∼1.12 mmol L −1 and 4.28 mmol L −1 for urine 1 and 2, respectively) may indicate urinary infection, since the positive nitrite result arises from the ability of bacteria to convert nitrate in nitrite species into the renal tissue . In plasma and serum, nitrite levels are not well defined, changing according to the body‘s situations, such as the intake of foods rich in nitrates and nitrites .…”
Section: Resultsmentioning
confidence: 99%
“…This may have limited any further biologically significant reductions in BP following UV-A exposure. Recently, we have shown that posture and the period of time of lying supine can alter both BP and plasma [NO 2 − ] (Liddle et al 2018 ), which emphasizes that posture should be carefully considered when conducting future research in this area.…”
Section: Methodsmentioning
confidence: 99%